miRNA and Degradome Sequencing Reveal miRNA and Their Target Genes That May Mediate Shoot Growth in Spur Type Mutant “Yanfu 6” - Song, Chunhui; Zhang, Dong; Zheng, Liwei; Zhang, Jie; Zhang, Baojuan; Luo, Wenwen; Li, Youmei; Li, Guangfang; Ma, Juanjuan; Han, Mingyu (Frontiers in Plant Science, 2017)
Spur-type growth habit apple tree is characterized by short internodes, increased fruiting spurs, and compact growth to enable easy flowering and laborsaving management. However, the molecular mechanisms of spur-type growth habits are not yet elaborated. In this study, miRNAs and their target genes expression in ‘Nagafu 2’ (CF) and its spur bud mutation ‘Yanfu 6’ (YF) shoot tips were detected. A total of 340 mature miRNAs including 198 known apple miRNAs and 142 potential novel miRNA candidates were found in the shoot tips. Comparison of miRNA expression in CF and YF revealed 135 different expression gene, most downregulated in YF. The YF shown low GA, ZR, IAA, and ABA content. Spraying GA can promote YF shoot growth. A regulatory network involved in plant hormone, miRNA and their targets for the molecular mechanism of YF architecture is proposed. MiRNA164, miRNA166, and miRNA171, and their targets associated with plant hormone regulated the shoot apical meristems (SAM) growth. MiRNA159, miRNA167, and miRNA396, and their target associated with plant hormone regulated the cell division and internode length. This study provides basis for further unravelling the mechanism of spur-type apple architecture.